Effective Factors on Caring Role of Parents of Children with Cerebral Palsy - Nasrin Alaee (Hamadan University of Medical Sciences, 2019)
Introduction: Parents of children with cerebral palsy are exposed to the complications of the child’s care; they need kinds of support to reduce problems of care for the child. Therefore, the current study was done in order to discover the factors that influence role of caring parents while taking care of the cerebral palsy child. Methods: This study is part of a qualitative study that was done in 2011-2013. Sampling was done based on goal-oriented and continued to saturate data. Thus، 33 participants including parents and family members of children with cerebral palsy that had been referred to Rehabilitation Centers in Tehran city and rehabilitation experts participated in this study. Data was collected through semi-structured interviews with each participant and analyzed through content analysis and continuous comparison of data. Results: The results of data analysis showed the concept of parental capital with two categories: parents’ personal ability (subcategories: mental and physical ability in care, the ability to communicate with others, belief in the spiritual value of the child) and parental situational resources (subcategories: the socio-economic status of the family, the availability of helping relatives, cooperation and partnership in the family). Conclusion: Parental capital as a supporting factor has an effectiveness on the sense of parents’ dominance on the situation of taking care of child; so، it is important to pay attention to the parents’ capital (internal and external) for educating and home care planning of affected child and family.